(untitled) (Anclajes, 2020)
This work aims to explore the ways in which archive appears in works by Mario Bellatin, with special attention given to his early pieces. We understand archive as a concept allowing us to analyze an operational field but also as an image or figuration, revealing the development of his work’s early stages. The journey starts with Las Mujeres de Sal (1986), Bellatin’s first book to be published and which, unlike his early works, is the only one that has not been republished. However, the Mexican writer has recently toyed with archive in other ways: a surviving fragment, an imagined element, a mystery, a rumor. We propose that resistance or inaccessibility to the text is a way to disguise it, that is, to confine it to a material or visual vacuum. Consequently, our search is both to discover what meanings are enclosed in that “closet” and to understand which of them, likewise, allow us to reacquire the work, causing it to escape negativity —its “coming out”.